Counseling of behavior healthy life in Purba Horison Village, Haranggaol District, Simalungun Regency, North Sumatra Province towards the industrial revolution 4.0 - Girsang, Bina Melvia; Simanullang, Rikki; Kusnadi; Ningrum, Haryati Asri; Pratiwi, Sri Aulia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Clean and Healthy Life Behavior (PHBS) is one way for the community to be able to maintain the quality of their health. In PHBS there are several indicators that are used as a reference in the implementation of PHBS, one of them washing hands with soap. Good clean and healthy behavior can prevent diseases that appear in the body. Based on the activities carried out by the 2019 KKN Student in Purba Horison Village, Haranggaol District, Simalungun Regency, North Sumatra Province, several problems in the Purba Horison Village have been resolved, namely the lack of public knowledge in the use and utilization of the potential of Natural Resources in the Village Purba Horizon, lack of public knowledge to produce a creative economy, the lack of community care Purba Horizon Village towards environmental cleanliness. With the existence of a clean and healthy life style, this will affect the health status of the community, especially the people of the Village of Horizon, who will be conducted a real work lecture as a form of activities carried out by students.